ANALISIS TARIKAN PERJALANAN PADA PERBELANJAAN SANGATTA TOWN CENTER DI KOTA SANGATTA - SETIAWAN, HENDRA (KURVA S JURNAL MAHASISWA, 2018)
Sangatta Town Center is the busiest area in Sangatta City. The number of buildings / shophouses in the area. Have a big influence on the attraction of this region of travel, Travel to Sangatta Town Center so it is necessary in the analysis of the model of travel attraction that led to the area                    The purpose of this study is to get a travel attraction model in Sangatta Town Center area and to know the value of R2 and F value, which is expected to be used to estimate the number of tug that goes to Sangatta Town Center                    Primary data obtained from the results of questionnaires survey conducted by random sampling, While the secondary data obtained from the Sangatta Twon Center in the form of data that is, the floor area, the number of visitors and the number of employees, and the dependent variable that is the total traction total.                Result from analysis of model of total travel with modeled form Y = 0,973 + 0,111X3 + 0,159X4 + 0,195X5 which have value R2 equal to 0,478. Shows the level of dependent variable relationship (independent variable) with independent variable (independent variable) at moderate correlation level this means that 47.8%. The total number of trips pull can be explained by the variable Y = Total Travel Drop, X3 = Last Education X4 = Work and X5 = Income and F test value (F count arithmetic> F table) (12.477> 2.68).